Design and Simulation Analysis of Lightweight HDPE Milk Bottle. Issue 1 (January 2018) - Huang, Hsing-Hui; Chen, Li-Wen; Lu, Wei-Hua; Lin, Wei-Cheng; Chen, Yung-Chuan
A lightweight design is proposed for a 2800 ml HDPE milk bottle. In designing the bottle, a three-dimensional elastic-plastic dynamic finite element model is first constructed to explore the effect of the bottle thickness on the critical load and stress distribution. The validity of the proposed model is confirmed by comparing the numerical results for the load-displacement response of the bottle with the experimental results. A parametric analysis is then performed to examine the effects of the body thickness and bottom thickness on the critical load and weight of the HDPE bottle. The results show that the critical load increases with an increasing body thickness, but is insensitive to the bottom thickness. Finally, a lightweight design is proposed in which the structural shape of the original bottle is retained, but the thickness is varied in different regions of the body in order to reduce the weight. It is shown that the redesigned bottle achieves the same maximum top-load 315 N, but reduces the weight by 21.4% compared to the reference design obtained in the parametric analysis.